Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/cbic.200800697
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Matrix‐Assisted Refolding of Histidine‐Tagged Proteins

Abstract: The formation of inclusion bodies (IBs)--amorphous aggregates of misfolded insoluble protein--during recombinant protein expression, is still one of the biggest bottlenecks in protein science. We have developed and analyzed a rapid parallel approach for matrix-assisted refolding of recombinant His(6)-tagged proteins. Efficiencies of matrix-assisted refolding were screened in a 96-well format. The developed methodology allowed the efficient refolding of five different test proteins, including monomeric and olig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 60 publications
2
13
0
1
Order By: Relevance
“…When compared to refolding in-solution, matrix-assisted refolding yields higher percentage of active protein. This was proved in a previous study in which, 5 tested proteins showed better refolding by matrix-assisted strategy than refolding in-solution [5]. There are several reports on the matrix-assisted refolding of ScFv using soft gel matrices.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…When compared to refolding in-solution, matrix-assisted refolding yields higher percentage of active protein. This was proved in a previous study in which, 5 tested proteins showed better refolding by matrix-assisted strategy than refolding in-solution [5]. There are several reports on the matrix-assisted refolding of ScFv using soft gel matrices.…”
Section: Resultssupporting
confidence: 57%
“…It is attributed that, high level expression of recombinant protein often results in protein aggregation, leads to the formation of inclusion bodies in vivo [4]. Several ScFv proteins had been expressed in E. coli in the past [5] and many of them were shown to be forming inclusion bodies. Even though, the formation of inclusion bodies is not desired, the proteins present in * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic properties of soluble and refolded Ta AlDH were similar (0.3 U/mg) and spectroscopic analysis showed them to be identical (Figure 4). Protein refolding from inclusion bodies is working for small-scale enzyme production [45] and so Ta AlDH was obtained in high yields as a functional enzyme. However, the method is very time consuming in comparison to soluble purification.…”
Section: Discussionmentioning
confidence: 99%
“…Although scFv are promising therapeutic agents, they are artificially designed proteins, which per‐se creates drawbacks. Expression of recombinant proteins in prokaryotes often yields inclusion bodies, such that it becomes necessary to solubilize and refold the protein . Single domain and stable proteins obtained from inclusion bodies can in principle be renatured by several means, including matrix‐assisted refolding procedures, or using osmolyte additives and chaperons .…”
Section: Introductionmentioning
confidence: 99%